The Effect of Service Quality on Customer Satisfaction: A Study of GOT Travel Batam - Yesa Natali R Tampubolon; Herman Novry Kristiansen Paninggiran (Brilliant International Journal Of Management And Tourism, 2026)
This study examines the effect of service quality on customer satisfaction at GOT Travel Batam, an online travel agent operating in Batam, Indonesia. The research addresses the problem of how different dimensions of service quality shape customer satisfaction in a digital travel-service context, where interactions are mediated by online platforms rather than face-to-face encounters. The main objective is to identify which dimensions of service quality significantly influence customer satisfaction and which dimension is the most dominant. A quantitative descriptive–verificative approach was applied using a survey of customers who had used GOT Travel Batam at least once in 2024–2025. A sample of 95 respondents was obtained through purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Service quality was measured through the SERVQUAL dimensions of tangibles, reliability, responsiveness, assurance, and empathy, while customer satisfaction was treated as the dependent variable. The results indicate that reliability and empathy have positive and significant effects on customer satisfaction, whereas tangibles, responsiveness, and assurance do not show significant effects in the proposed model. Empathy emerges as the most dominant dimension, followed by reliability. Overall, the findings suggest that online travel customers place greater emphasis on personal attention and dependable service performance than on physical evidence or mere response speed.In conclusion, service quality remains critical for customer satisfaction in digital OTAs, but the hierarchy of dimensions shifts empathy and reliability become the dominant drivers while tangibles, responsiveness, and assurance lose their direct influence